ACTIVATION REACTION ON THE ELECTROENCEPHALOGRAM IN SUBSTANCE DEPENDENT PATIENTS: LINKS TO ADDICTION STUDIES AND PSYCHOLOGICAL FACTORS AND CHANGES IN NEUROFEEDBACK TRAINING - M. e Melnikov (Бюллетень сибирской медицины, 2014)
Depth of activation reaction (α-activity suppression during the eyes-opening task) is considered to be an important quantitative characteristic of α-band brainwaves. Activation reaction was assessed from O1 and O2 leads in 31 male substance dependent subjects. In 7 cases it was measured twice: before and after α- or β-brainwave biofeedback training. The correlations were found between grade of α suppression in eyes-opening task and attitude towards disease and treatment, personality maturity, and level of pathological personality traits. Activation reaction was significantly improved by α-training and non-significantly diminished after β-1-training.